2021
DOI: 10.4103/ams.ams_75_20
|View full text |Cite
|
Sign up to set email alerts
|

Two-Point versus Three-Point Fixation in the Management of Zygomaticomaxillary Complex Fractures

Abstract: Introduction: The zygoma plays an important role in the facial contour for both cosmetic and functional reasons; therefore, zygomatic bone injuries should be properly diagnosed and adequately treated. Comparison of various surgical approaches and their complications can only be done objectively using outcome measurements that require a protocol for management and long-term follow-up. The objectives of this study were to compare the efficacy of zygomatic bone after treatment with open reduction int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
10
2
Order By: Relevance
“…They noted that treating ZMC complicated fractures with approach involving three-point fixation and tolerant rigid fixation of fractured sections of bone leads to a reduced frequency of complications that are proportionate to the intensity of traumatic injury. [ 25 , 26 ] Gadkari et al [ 16 ] study strongly suggested, however, that three-point fixation offers superior outcomes and upholds stability of site of fracture in all three dimensional planes . Three-point visualization and fixation led to undesirable consequences in the trial, like postoperative visible scars.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that treating ZMC complicated fractures with approach involving three-point fixation and tolerant rigid fixation of fractured sections of bone leads to a reduced frequency of complications that are proportionate to the intensity of traumatic injury. [ 25 , 26 ] Gadkari et al [ 16 ] study strongly suggested, however, that three-point fixation offers superior outcomes and upholds stability of site of fracture in all three dimensional planes . Three-point visualization and fixation led to undesirable consequences in the trial, like postoperative visible scars.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there are complications that occur less frequently with fewer fixation points. Studies have reported that postoperative facial and neurological complications were less common in patients who underwent two-point fixation than three-point fixation [ 7 ]. and that scar formation occurred more frequently in two-point fixation than one-point fixation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, multiple studies have compared two-point versus three-point fixation [6][7][8]. One study, which compared onepoint and two-point fixation using X-rays, argued that twopoint fixation was superior for bone stability to one-point fixation [9].…”
Section: Introductionmentioning
confidence: 99%
“…1 Following the nasal bone, zygoma is the second most prominent bone of the midface; therefore, it is frequently injured bone seen in daily clinical practice. 2 Zygoma is fractured due to various trauma, including accidental injuries, personal assaults, sports injuries, fall from height, and road traffic accidents (RTAs). 3 As in any fracture of the body, the assessment consists of a detailed history of trauma (such as the cause, mechanism, and duration), clinical evaluation, and radiologic investigations such as computed tomography (CT).…”
mentioning
confidence: 99%
“…The zygomaticomaxillary complex (ZMC) fractures refer to the osseous disruption of all buttresses of zygomatic (malar) bone: zygomaticomaxillary, frontozygomatic, zygomatico-sphenoid, and zygomaticotemporal 1 . Following the nasal bone, zygoma is the second most prominent bone of the midface; therefore, it is frequently injured bone seen in daily clinical practice 2 . Zygoma is fractured due to various trauma, including accidental injuries, personal assaults, sports injuries, fall from height, and road traffic accidents (RTAs) 3 .…”
mentioning
confidence: 99%